Research of IOTs Complex Event for Supply Chain Application - Li Juntao; Cheng Xiaolin; Lin Gang (Institute of Advanced Engineering and Science, 2013)
In order to solve the logic fault of Internet of things technology applied in the supply chain system, this paper presents processing framework which is based on the context of complex event processing technology.At first, paper analysis the hierarchy of processing framework oriented supply chain applications, and then put forward the situation model of event flow based on complex event, including the establishment of the model, the definition of the event as well as the event description language.The context-aware framework based on complex event processing technology can solve the problem that the underlying data cannot be used efficiently bythe upper, which is proved bya typical case existingin the supply chain.As a result, it can improve the reaction speed of the supply chain system, reduce supply chain inventory as well as bullwhip effect. DOI: http://dx.doi.org/10.11591/telkomnika.v11i8.3028